Karl Marx : Greatness and Illusion - Stedman Jones, Gareth (London Allen Lane, an imprint of Penguin Books, 2016)
A deeply original and illuminating account of Marx's journey through the intellectual history of the nineteenth century... a profound reappraisal and a gripping read' Christopher Clark 'Rich and deeply researched' John Gray As the nineteenth century unfolded, its inhabitants had to come to terms with an unparalleled range of political, economic, religious and intellectual challenges. Distances shrank, new towns sprang up, and ingenious inventions transformed the industrial landscape.
Include Maps, Illustrations, Notes and References, Bibliography and Index.
Keywords: Marx, Karl, 1818-1883 -- Europe -- Philosophy, Marxist -- Politics and government